SUR2A: How to use this protein in the therapy of ischemic heart disease? - Jovanović, Aleksandar (Archives of Pharmacy, 2020)
SUR2A is an atypical ABC protein serving as a regulatory subunit of ATP-sensitive K+ (KATP) channels. In experimental animals, it has been found that an increase in myocardial level of this protein protects the heart against different types of metabolic stresses, including ischaemia. Increase in SUR2A leads to increase in number of fully-assembled KATP channels, which is associated with earlier channel activation during ischaemia as well as increased production of ATP by enzymes that are physically associated with the channel subunits. Activation of KATP channels shorten action membrane potential to prevent Ca2+ influx while ATP production increases subsarcolemmal ATP levels providing energy for vital energy-dependent processes at this localisation. The most recent findings are that SUR2A might also regulate expression of genes that are important in cardioprotection. How to increase SUR2A expression in an efficient and safe manner has been considered. Two possible approaches have been found to be promising. One is gene therapy approach with adenovirus containing SUR2A which was successful at the cellular level and the other was oral nicotinamide, a form of vitamin B3, which was efficient under ex vivo conditions. Based on all these findings, we believe that SUR2A-based strategies against heart ischaemia deserve to be further elucidated and tested. A therapy of ischaemic heart disease exploiting endogenous cardioprotective factors, including SUR2A, would be an excellent adjunct to current therapeutic strategies of ischaemic heart disease and other cardiovascular diseases where increase in cardiac resistance to stress would be beneficial.
Keywords: SUR2A; ATP-sensitive K channels; Cardioprotection